Os jovens agricultores familiares e a reproduçao geracional na agricultura familiar : Estudo de caso dos jovens residentes no município de Faxinal do Soturno - Brasil - Coradini, Lucas (Mundo Agrario.)
This study examines how the youth's Professional projects in new generation of family farmers are prepared and the perspective of reproduction of the familiar mode of production. The sociological task is to specify the distinctive features of the situation of the youth in family farming, seeking to identify the elements considered in the preparation of their professional projects. Qualitative data were produced by a case study of young farmers who lives in the city of Faxinal do Soturno, a municipality belonging to the fourth colony of Italian immigration in Rio Grande do Sul/Brazil. We performed 36 interviews, consisting of open questions, adopting a semi-structured script, wich were examined by de method of content analysis. Among the results, were observed a context marked by professional projects that breaks with the succession of the family farm work. The negative ratings on agricultural work stand out, particularly on issues related to health, salubrity of work and conditions of aging in rural areas. Family and emotional issues, and also specific aspects of the juvenile condition, marked by the pursuit of autonomy and emancipation, permeate the professional projects in development and show a complex analytical framework, wich amplify the explanatory factors of migration of youth.